Determine the area of a non-symmetrical large surface by using parametric equation for undergraduate students - Affendi, Nurul Affaeeza; Harun, Nurzalina; Sadikin, Zubaidah; Rathi, Sidik; Mohd Sidek, Nur Zafirah; Batcha, Siti Rahimah; Salim Nasir, Mohd Agos (Academica Press Solutions, 2024)
This prototype method was introduced to society for various purposes mainly for studies and construction management. The calculation of the area of non-symmetrical shapes often presents a challenge in mathematics and various fields of science and engineering. Traditional methods, such as integration and geometric decomposition, may become impractical and time consuming. In such case, parametric equations provide a powerful and versatile tool for area determination only by using Microsoft excel trendline. This abstract explores the application of parametric equations in calculating the area of non-symmetrical shapes. Furthermore, Microsoft excel trendline shows the abstract highlights practical applications of this technique in fields such as engineering, physics, computer graphics and biology, where complex and irregular shapes frequently arise. Examples of specific non-symmetrical shapes and their corresponding parametric equations will be presented, illustrating the versatility and efficiency of this method. Parametric equations describe the relationship between two or more variables using one or more parameters. Impact on this is they are particularly useful when dealing with shapes that cannot be conveniently expressed using standard functions. By parameterizing the coordinates of points and dividing the area by segment along the shape’s boundary, the area enclosed by the curve can be determined through the application of substitution of definite integrals formula and the total area can be finalized by sum up all the area by segment of the surface.